Some iterative methods for the solution of a symmetric indefinite KKT system - Bonettini, Silvia; Ruggiero, Valeria (Computational optimization and applications, 2007)
This paper is concerned with the numerical solution of a Karush-Kuhn-Tucker system. Such symmetric indefinite system arises when we solve a nonlinear programming problem by an Interior-Point (IP) approach. In this framework, we discuss the effectiveness of two inner iterative solvers: the method of multipliers and the preconditioned conjugate gradient method. We discuss the implementation details of these algorithms in an IP scheme and we report the results of a numerical comparison on a set of large scale test-problems arising from the discretization of elliptic control problems. [PUBLICATION ABSTRACT]